Analysis of Phenolic, Flavonoid Content, and Antioxidant Activity of Combination of Pumpkin Leaves (Cucurbita moschata Durch.) and Aibika Leaves (Abelmoschus manihot L.) Fractions - Ari Sartinah; Yamin Yamin; Hasnawati Hasnawati; Suryani Suryani; Nur Illiyyin Akib; Hikmawati Supu (Jurnal Kartika Kimia, 2026)
This study aims to determine the total phenolic and flavonoid content of ethyl acetate fractions from pumpkin (Cucurbita moschata Durch.) and aibika (Abelmoschus manihot L.) leaves, and to evaluate the antioxidant activity of their combined fractions. Analysis of total phenolics and flavonoids content was carried out using UV-Vis spectrophotometry with gallic acid (phenolics) and quercetin (flavonoids) as standards. Antioxidant potential testing was carried out using the DPPH method. The results showed that the phenolics content of the ethyl acetate fraction of PLand ALwas 60.81 and 56.47 mgEAG/g, respectively, while the total flavonoids content of the ethyl acetate fraction of PLand ALwas 64.54 and 55.07 mgEK/g, respectively. The IC50 value of the combination of ethyl acetate fractions of PLand ALwith a ratio of 3:2 was 4.686 μg/mL, while the single ethyl acetate fractions of PLand ALwere 7.040 and 7.549 μg/mL, respectively. This indicates that increasing antioxidant activity can be done by combining fractions from two or more types of plants.